PENGARUH PENDAPATAN PAJAK KENDARAAN BERMOTOR TERHADAP PENDAPATAN ASLI DAERAH DI MERAUKE - Marthen A I Hahumury (Faculty Of Economics and Business, Musamus University, 2018)
Effect of Motor Vehicle Tax Revenues on Regional Original Revenues in Merauke This study aims to analyze the effect of motor vehicle tax revenue on regional original income in Merauke by using quantitative data analysis with data analysis techniques used namely simple regression analysis to analyze the influence between independent variables (X) on the dependent variable (Y) with the help of ibm programs. Based on the results of data analysis and hypothesis testing described in the previous chapters, it is concluded that motor vehicle tax has an effect on and significant on regional original income, which means that there is an increase in motorized vehicle tax revenues that have a direct impact on increasing regional original income in Merauke. Keywords: Effect Influence, Income of Motorized Taxes on Regional Original Revenues in Merauke